2012
DOI: 10.1016/j.rmed.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Different risk factors between interstitial lung disease and airway disease in rheumatoid arthritis

Abstract: The differential associations of ILD and AD with various clinical and genetic factors suggest that ILD and AD have distinct etiologies in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(152 citation statements)
references
References 48 publications
9
138
1
4
Order By: Relevance
“…In contrast, anti-centromere antibodies are associated with limited cutaneous disease and increased risk of PH [19,57]. In RA, rheumatoid factor and anti-citrullinated protein antibodies have been associated with ILD [58,59,60]. In PM/DM, anti-Jo-1 and anti-SSA/Ro antibodies have also been found to be linked with severe and extensive ILD [61].…”
Section: Pulmonary ‘Disease Activity' In Monitoringmentioning
confidence: 99%
“…In contrast, anti-centromere antibodies are associated with limited cutaneous disease and increased risk of PH [19,57]. In RA, rheumatoid factor and anti-citrullinated protein antibodies have been associated with ILD [58,59,60]. In PM/DM, anti-Jo-1 and anti-SSA/Ro antibodies have also been found to be linked with severe and extensive ILD [61].…”
Section: Pulmonary ‘Disease Activity' In Monitoringmentioning
confidence: 99%
“…Numerous studies have found that BR precedes RA often by 20-30 years 1,8,13,14 , supporting the hypothesis that BR may be involved in the pathogenesis of RA 1,8,13,14 8,13,18,19 . Initially no link between anti-CCP and lung disease was found 20 , but two studies have reported an association between anti-CCP and airways disease 21 and interstitial lung disease 22 in patients with established RA.…”
Section: Introductionmentioning
confidence: 99%
“…Yap›lan bir çal›flmada RA'l› hastalarda 65 yafl›n üzerinde olman›n ‹AH geliflme riskini 4 kat art›rd›¤› gösterilmifltir. [34] Sigara, RA geliflimi için bir risk faktörüdür. [35] ‹çilen paket/y›l miktar› artt›kça RA geliflme riski de o oranda art›fl göste-rir.…”
Section: Risk Faktörleriunclassified